EXTENSION OF SOLUTIONS OF NONLINEAR ORDINARY DIFFERENTIAL EQUATIONS - Bidarkar, Sunil N. (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
In this paper we present an extension of solutions of examples of nonlinear ordinary differential equations. The solutions are obtained by using the different methods. For illustration some examples are presented. The first method is, procedure for obtaining explicit and implicit formulas for the solution of various ordinary differential equations and the second one is by using basic existence and uniqueness theorem. Key words: Â Nonlinear ordinary differential equation, explicit and implicit solutions, existence, uniqueness, formal identity.